Analysis of Differences in Knowledge of Pregnant Women About 4t Risks in the Work Area of the Pinembani Community Health Center, Pinembani District, Donggala Regency through Health Education - Serlis Kris Jesni Woso; Jamaluddin Sakung; Muh. Jufri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
The mortality rate for pregnant women occurs due to direct and indirect causes. The immediate cause of maternal death is usually closely related to the condition of the mother's health since pregnancy, childbirth and the puerperium. While the indirect reasons are more connected to social, economic, educational, cultural needs and lack of knowledge, the attitudes of the community, especially pregnant women, about the risk of 4T (too young, too old, too many children, too close to pregnancy) and Three Too Late (again late making decisions, late in bringing to health facilities, late in getting health services). The purpose of this study was to determine the differences in knowledge before and after about the risk of 4T in the working area of the Pinembani Public Health Center, Pinembani District, Donggala Regency through Health Counseling. This type of research is analytic with an experimental research type approach using a one-group pretest-posttest design. Namely, before doing counselling, the respondents were given a questionnaire (pretest) then after the counselling was carried out, the respondents were provided with a questionnaire for the second time (posttest) then the researcher compared the pretest-posttest results. The results showed that the mean value before (pretest) was 70.98 with a standard deviation of 15.460. At the same time, the mean value after (posttest) was 89.51 with a standard deviation of 11.169. The results of statistical tests show that the value of p (p-Value) = 0.000, which means (p> 0.05), there is a difference in the knowledge of pregnant women about the risk of 4T through health education. This research is expected for health workers at the Pinembani Public Health Center to provide more counselling or information about health at the posyandu to increase the knowledge of pregnant women.